How University students in Bangladesh engage with ChatGPT: A qualitative study - Mir Hasib; Md. Shariful Islam (PLoS ONE, 2025)
This study examined university students’ perceptions and practices of using ChatGPT through a qualitative approach, employing semi-structured, in-depth interviews with 20 Khulna University students. Using thematic analysis, the research identified key themes, including both academic and non-academic motivations, with applications ranging from assignments and research to entertainment. Despite limitations such as false references and predetermined feedback, students found ChatGPT efficient and useful both inside and outside the classroom. However, concerns about academic integrity arose, as some students devised creative ways to bypass existing plagiarism detection systems. Ethical considerations emerged regarding responsible AI use, underscoring the need for clear guidelines and training to ensure proper referencing and the development of critical thinking skills. Future research should focus on continuous evaluation and the implementation of support services to encourage the responsible integration of ChatGPT in university settings.